Management of Dairy Farm using PHP and MySQL - Harris Charles F; H. Jayamangala (International Journal of Advanced Research in Science, Communication and Technology, 2024)
A survey was prepared by the Dairy farming Working Group together with invited milk recording organizations. This paper is one part of this project and focuses on management and organizational questions. The management of recording organizations in the current climate of growing competition is more challenging than ever. The main part of this approach is how to develop a clear relationship with customers and how to provide value to farmers in regard to collected data and samples. New tools of analysis are already very common in some countries, while other participants are now focusing on maximizing increased efficiency in data capturing and processing. In those countries whose workflow is technician-based, training and certification are major components in improving human resources. The reporting of results back to farmers is also a very challenging area. The use of paper and pdf-reports is very common, but new online technologies and smartphone usage now provide new opportunities for farmers to manage information. Real value is created by additional analyses from identified milk samples. The goal was to develop a program that is flexible enough to be useful in a wide variety of management systems by providing reports suited to the individual producer. The existing program already collects farmers, employees, deliveries and their databases respectively other maintenance procedures and performance records